Cathode composite catalyst layer and preparation method thereof, membrane electrode and fuel cell

By setting a strong anchoring carbon layer between the cathode catalytic layer of the fuel cell and the proton exchange membrane to capture Pt2+ ions, the performance degradation caused by Pt loss and membrane electrode durability are solved, and higher Pt utilization and better Good membrane electrode durability.

CN119133488APending Publication Date: 2024-12-13DONGFENG MOTOR GRP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411106808.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The oxidation failure and loss of metal Pt in fuel cells lead to performance attenuation and desistance of durability, especially at the cathode, which leads to the degradation of the proton exchange membrane.

Method used

A strongly anchored carbon layer is arranged between the cathode catalytic layer and the proton exchange membrane. The Pt2+ affected by the electric field is captured through the anchor positioning points in the carbon layer, avoiding its migration and forming a Pt band, thereby improving the utilization rate of Pt and the membrane electrode. Durability.

Benefits of technology

It effectively avoids performance degradation and proton exchange membrane degradation caused by Pt loss, improves the durability and electrochemical performance of membrane electrodes, and improves the utilization rate of Pt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133488A_ABST
    Figure CN119133488A_ABST
Patent Text Reader

Abstract

The invention provides a cathode composite catalyst layer and a preparation method thereof, a membrane electrode and a fuel cell, and belongs to the field of fuel cells. The cathode composite catalyst layer comprises: a strongly anchored carbon layer; the slurry of the strong anchoring carbon layer comprises the following raw materials: a strong anchoring functional material, a solvent and a Nafion solution, and the strong anchoring functional material is a non-metallic element doped carbon material; and a cathode catalyst layer; the cathode catalyst layer is arranged on one side of the strong anchoring carbon layer, and the cathode catalyst layer contains a Pt element; wherein the strong anchoring carbon layer is arranged between the cathode catalyst layer and the proton exchange membrane. The strong anchoring carbon layer is arranged between the cathode catalyst layer and the proton exchange membrane, and Pt < 2 + > which is migrated to the proton exchange membrane side under the action of an electric field is captured through an anchoring point formed by non-metallic elements in the carbon layer, so that performance reduction caused by Pt loss and proton exchange membrane degradation caused by formation of a Pt belt are avoided, and meanwhile, the utilization rate of Pt is increased; therefore, the durability of the membrane electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fuel cell technology, and in particular to a cathode composite catalyst layer and a preparation method, a membrane electrode and a fuel cell. Background Art

[0002] Hydrogen energy is an important part of my country's future energy system. Fuel cells are one of the important areas of hydrogen energy development. In recent years, the state and government have vigorously developed fuel cells through the construction of hydrogen fuel cell demonstration operation city clusters, two vertical and four horizontal "hydrogen energy highways", etc. However, the cost, durability and reliability of fuel cells have always restricted the commercial application of fuel cells.

[0003] In the actual operation of fuel cells, the oxidation failure and loss of metal Pt is one of the important reasons for the performance degradation and durability reduction of fuel cells. Due to the influence of potential, this phenomenon is particularly obvious at the cathode. During the oxidation-reduction process of metal Pt, part of the metal Pt is oxidized to Pt 2+ After that, it moves from high potential to low potential under the action of electric field. Due to the lack of suitable deposition sites, it will eventually be reduced to form Pt band on the proton exchange membrane side. The formation of Pt band will not only cause the decline of cathode catalytic performance, but also seriously cause the degradation of proton exchange membrane, and finally lead to the decline of membrane electrode durability. Therefore, how to improve the durability of membrane electrode of fuel cell is a technical problem that needs to be solved urgently. Summary of the invention

[0004] The present application provides a cathode composite catalyst layer and a preparation method, a membrane electrode and a fuel cell to solve the following technical problem: how to improve the durability of the membrane electrode of the fuel cell.

[0005] In a first aspect, the present application provides a cathode composite catalytic layer, the cathode composite catalytic layer comprising:

[0006] Strong anchoring carbon layer; the raw materials of the slurry of the strong anchoring carbon layer include: strong anchoring functional material, solvent and Nafion solution, the strong anchoring functional material is a carbon material doped with non-metallic elements; and

[0007] A cathode catalyst layer; the cathode catalyst layer is disposed on one side of the strongly anchored carbon layer, and the cathode catalyst layer contains a Pt element;

[0008] Wherein, the strongly anchored carbon layer is arranged between the cathode catalyst layer and the proton exchange membrane.

[0009] Optionally, the non-metallic elements include: one or more of O, N, S and P.

[0010] Optionally, the carbon material includes: one or more of carbon black, porous carbon, carbon fiber, graphite carbon and carbon nanotubes.

[0011] Optionally, the mass ratio of the strong anchoring functional material to the perfluorosulfonic acid resin in the Nafion solution is 1:(1.0-1.2).

[0012] Optionally, the raw materials of the slurry of the cathode catalyst layer include: a catalyst, a Nafion solution and a solvent.

[0013] Optionally, the catalyst includes one or more of a Pt / C catalyst and a Pt alloy catalyst.

[0014] In a second aspect, the present application provides a method for preparing a cathode composite catalyst layer according to any one of the embodiments of the first aspect, the method comprising:

[0015] The strong anchoring functional material is mixed with a solvent and a Nafion solution, and then dispersed to obtain a slurry of a strong anchoring carbon layer;

[0016] The catalyst is mixed with a solvent and a Nafion solution, and then dispersed to obtain a slurry of a cathode catalyst layer;

[0017] Applying the slurry of the strong anchoring carbon layer to the surface of one side of the proton exchange membrane to obtain the strong anchoring carbon layer supported on the proton exchange membrane;

[0018] The slurry of the cathode catalyst layer is coated on the surface of the strongly anchored carbon layer on the side away from the proton exchange membrane to obtain a cathode composite catalyst layer supported on the proton exchange membrane.

[0019] Optionally, the coating is performed by a spraying process.

[0020] In a third aspect, the present application provides a membrane electrode, the membrane electrode comprising:

[0021] Proton exchange membrane;

[0022] The cathode composite catalyst layer as described in any one of the embodiments of the first aspect; the cathode composite catalyst layer is arranged on one side of the proton exchange membrane;

[0023] Anode catalyst layer; the anode catalyst layer is arranged on the other side of the proton exchange membrane;

[0024] Gas diffusion layer; the gas diffusion layer is arranged on a side of the cathode composite catalyst layer and the anode catalyst layer away from the proton exchange membrane.

[0025] In a fourth aspect, the present application provides a fuel cell, comprising the membrane electrode as described in the embodiment of the third aspect.

[0026] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0027] The present application provides a cathode composite catalyst layer, which includes: a strongly anchored carbon layer; the raw materials of the slurry of the strongly anchored carbon layer include: a strongly anchored functional material, a solvent and a Nafion solution, wherein the strongly anchored functional material is a carbon material doped with a non-metallic element; and a cathode catalyst layer; the cathode catalyst layer is arranged on one side of the strongly anchored carbon layer, and the cathode catalyst layer contains a Pt element; wherein the strongly anchored carbon layer is arranged between the cathode catalyst layer and the proton exchange membrane. By arranging a strongly anchored carbon layer between the cathode catalyst layer and the proton exchange membrane, the Pt that migrates to the proton exchange membrane side under the action of the electric field is captured by the anchoring points formed by the non-metallic elements in the carbon layer. 2+ , avoiding performance degradation due to Pt loss and proton exchange membrane degradation due to the formation of Pt bands, while improving the utilization of Pt, thereby improving the durability of the membrane electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0030] Figure 1 A flow chart of a method for preparing a cathode composite catalyst layer provided in an embodiment of the present application;

[0031] Figure 2 A schematic diagram of the structure of a membrane electrode provided in an embodiment of the present application;

[0032] Figure 3 The membrane electrode durability operating condition diagram provided for Examples 1 and 2 of the present application and Comparative Example 1;

[0033] Figure 4 Cyclic voltammetry test diagrams provided for Examples 1 and 2 and Comparative Example 1 of the present application;

[0034] Figure 5 Polarization curve test diagrams provided for Examples 1 and 2 and Comparative Example 1 of the present application;

[0035] Figure 6 This is a hydrogen permeation current density test diagram provided for Examples 1 and 2 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0037] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0038] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "the following at least one item (items)" or similar expressions refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.

[0039] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0040] The creative ideas of this application are:

[0041] In the actual operation of fuel cells, the oxidation failure and loss of metal Pt is one of the important reasons for the performance degradation and durability reduction of fuel cells. Due to the influence of potential, this phenomenon is particularly obvious at the cathode. During the oxidation-reduction process of metal Pt, part of the metal Pt is oxidized to Pt 2+ After that, it moves from high potential to low potential under the action of electric field. Due to the lack of suitable deposition sites, it will eventually be reduced to form Pt band on the proton exchange membrane side. The formation of Pt band will not only cause the decline of cathode catalytic performance, but also seriously cause the degradation of proton exchange membrane, and finally lead to the decline of membrane electrode durability.

[0042] Based on the above technical problems, the present invention creatively sprays a layer of strong anchoring carbon layer on the cathode side close to the proton exchange membrane side, and captures the Pt that migrates to the proton exchange membrane side under the action of the electric field through the anchoring points in the carbon layer. 2+ , avoiding performance degradation due to Pt loss and proton exchange membrane degradation caused by the formation of Pt bands, while improving the utilization rate of Pt and the durability of the membrane electrode, and then preparing the cathode catalyst layer, the anode catalyst layer and the gas diffusion layer, and finally forming a membrane electrode with a structure in which the gas diffusion layer, the cathode catalyst layer, the strongly anchored carbon layer, the proton exchange membrane, the anode catalyst layer and the gas diffusion layer are distributed in sequence.

[0043] Therefore, the present application creatively sets a strong anchoring carbon layer between the cathode catalyst layer and the proton exchange membrane to solve the problem of avoiding performance degradation due to Pt loss and proton exchange membrane degradation caused by the formation of Pt bands during the use of the membrane electrode, thereby improving the utilization rate of Pt and further improving the durability of the membrane electrode of the fuel cell.

[0044] The present application provides a cathode composite catalytic layer, the cathode composite catalytic layer comprising:

[0045] Strong anchoring carbon layer; the raw materials of the slurry of the strong anchoring carbon layer include: strong anchoring functional material, solvent and Nafion solution, the strong anchoring functional material is a carbon material doped with non-metallic elements; and

[0046] A cathode catalyst layer; the cathode catalyst layer is disposed on one side of the strongly anchored carbon layer, and the cathode catalyst layer contains a Pt element;

[0047] Wherein, the strongly anchored carbon layer is arranged between the cathode catalyst layer and the proton exchange membrane.

[0048] In the embodiment of the present application, based on the Pt loss mechanism, Pt 2+ Ions will migrate from the cathode catalyst layer to the proton exchange membrane side under the action of the electric field and form a Pt band. Therefore, the high anchor carbon layer is located between the cathode catalyst layer and the proton exchange membrane, which plays a role in Pt 2+ Ion capture.

[0049] In some embodiments, the non-metallic element includes one or more of O, N, S and P.

[0050] In some embodiments, the carbon material includes one or more of carbon black, porous carbon, carbon fiber, graphite carbon and carbon nanotubes.

[0051] In the above-mentioned embodiment, the O, N, S, and P elements in the strong anchoring functional material can form a bond with Pt to form an anchoring effect, and at the same time have good conductivity and will not affect the conductivity of the membrane electrode.

[0052] In some embodiments, the mass ratio of the strong anchoring functional material to the perfluorosulfonic acid resin in the Nafion solution is 1:(1.0-1.2).

[0053] It should be noted that Nafion solution (Nafion polymer dispersant) contains polymer in its chemically stable liquid form, making the processing process easier. Typical applications include: the manufacture of thin films and coating formulations for fuel cell membranes, catalyst coatings, sensors and various electrochemical applications. The mass fraction of perfluorosulfonic acid resin in Nafion solution is 5% to 30%.

[0054] In the above embodiment, the perfluorosulfonic acid resin in the Nafion solution can be used as an adhesive for the carbon layer on the one hand, and can also act as a proton conductor on the other hand. The mass ratio of the strong anchoring functional material to the perfluorosulfonic acid resin is controlled to be strong anchoring functional material: perfluorosulfonic acid resin = 1: (1.0-1.2). If the mass ratio is too high (too little perfluorosulfonic acid resin), it will not have enough adhesive effect and the structure will be unstable; if the mass ratio is too low (too much perfluorosulfonic acid resin), it will increase the oxygen mass transfer resistance of the catalytic layer. Exemplarily, the mass ratio of the strong anchoring functional material to the perfluorosulfonic acid resin can be 1:1, 1.00:1.05, 1.0:1.1, 1.00:1.15, 1.0:1.2, etc.

[0055] In some embodiments, the raw materials of the cathode catalyst layer slurry include: a catalyst, a Nafion solution and a solvent.

[0056] In some embodiments, the catalyst includes one or more of a Pt / C catalyst and a Pt alloy catalyst.

[0057] Figure 1 A flow chart of a method for preparing a cathode composite catalyst layer provided in an embodiment of the present application.

[0058] Based on a general inventive concept, see Figure 1 The present application provides a method for preparing a cathode composite catalyst layer as described in any one of the above embodiments, the method comprising:

[0059] S1, mixing the strong anchoring functional material with the solvent and the Nafion solution, and then dispersing them to obtain a slurry of the strong anchoring carbon layer;

[0060] S2, mixing the catalyst with the solvent and the Nafion solution, and then dispersing them to obtain a slurry of the cathode catalyst layer;

[0061] S3, coating the slurry of the strong anchoring carbon layer on the surface of one side of the proton exchange membrane to obtain the strong anchoring carbon layer supported on the proton exchange membrane;

[0062] S4. Coating the cathode catalyst layer slurry onto the surface of the strongly anchored carbon layer on the side away from the proton exchange membrane to obtain a cathode composite catalyst layer supported on the proton exchange membrane.

[0063] In some embodiments, the coating is performed by a spray coating process.

[0064] In the above embodiment, the spraying process can ensure that the strongly anchored carbon layer has a certain void distribution to avoid mass transfer influence, and at the same time can be in close contact with the proton exchange membrane to reduce the contact resistance between the carbon layer and the proton exchange membrane.

[0065] In some embodiments, the solvent is a common organic solvent such as ethanol or isopropanol.

[0066] In some embodiments, the equipment used for the dispersion includes common dispersion equipment such as mechanical stirring, homogenizer, and water bath ultrasound.

[0067] The product prepared by the method for preparing a cathode composite catalytic layer is the above-mentioned cathode composite catalytic layer. The chemical composition and microstructure of the cathode composite catalytic layer prepared by the method for preparing a cathode composite catalytic layer can refer to the above-mentioned embodiment. Since the method for preparing a cathode composite catalytic layer adopts part or all of the technical solutions of the cathode composite catalytic layer embodiment, it has at least all the beneficial effects brought by the technical solutions of the cathode composite catalytic layer embodiment, which will not be described one by one here.

[0068] Figure 2 A schematic diagram of the structure of a membrane electrode provided in an embodiment of the present application.

[0069] Based on a general inventive concept, see Figure 2 The present application provides a membrane electrode, the membrane electrode comprising:

[0070] Proton exchange membrane;

[0071] The cathode composite catalyst layer as described in any one of the above embodiments; the cathode composite catalyst layer is arranged on one side of the proton exchange membrane;

[0072] Anode catalyst layer; the anode catalyst layer is arranged on the other side of the proton exchange membrane;

[0073] Gas diffusion layer; the gas diffusion layer is arranged on a side of the cathode composite catalyst layer and the anode catalyst layer away from the proton exchange membrane.

[0074] The membrane electrode provided in the present application has a structure in which a gas diffusion layer, a cathode catalyst layer, a strongly anchored carbon layer, a proton exchange membrane, an anode catalyst layer and a gas diffusion layer are distributed in sequence.

[0075] The ECSA attenuation rate of the membrane electrode provided in this application after 2000 cycles is ≤35%, and the rated voltage is ≥0.570V@2000mA / cm 2 , hydrogen permeation current density ≤2.950mA / cm2@0.4V.

[0076] Based on a general inventive concept, the present application provides a fuel cell, which includes the membrane electrode described in the above embodiment.

[0077] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.

[0078] Example 1

[0079] This embodiment provides a method for preparing a membrane electrode, comprising the following steps:

[0080] 1) Weigh 0.3 g of S-doped carbon fiber, stir and mix with 5.77 g of Nafion solution (the mass fraction of perfluorosulfonic acid resin in the Nafion solution is 5.2%) and 10 g of isopropanol, and disperse with a dispersing device to prepare a strongly anchored carbon layer slurry;

[0081] 2) 0.679 g of TKK 47% Pt / C catalyst was moistened with a small amount of water, 4.10 g of Nafion solution and 21 g of isopropanol were added and mixed evenly, and dispersed using a dispersing device to prepare a catalyst layer slurry;

[0082] 3) spraying the strongly anchored carbon layer slurry prepared in step 1) on the surface of one side of a 72×72 mm proton exchange membrane through a spraying process to form a proton exchange membrane with a high anchored carbon layer load;

[0083] 4) spraying the catalyst layer slurry prepared in step 2) onto the surface of the high anchor carbon layer formed in step 3) on the side away from the proton exchange membrane to form a cathode catalyst layer;

[0084] 5) spraying the catalyst layer slurry prepared in step 2) on the other side of the proton exchange membrane to form an anode catalyst layer;

[0085] 6) The gas diffusion layer is respectively mounted on the surface of the cathode catalyst layer and the anode catalyst layer away from the proton exchange membrane, and then divided to form a 25 cm 2 of membrane electrode.

[0086] Example 2

[0087] This embodiment provides a method for preparing a membrane electrode, comprising the following steps:

[0088] 1) Weigh 0.4 g of N-doped carbon nanotubes, stir and mix with 9 g of Nafion solution (the mass fraction of perfluorosulfonic acid resin in the Nafion solution is 5.2%) and 12 g of isopropanol, and disperse them using a dispersing device to prepare a strongly anchored carbon layer slurry;

[0089] 2) 0.679 g of TKK 47% Pt / C catalyst was moistened with a small amount of water, 4.10 g of Nafion solution and 21 g of isopropanol were added and mixed evenly, and dispersed using a dispersing device to prepare a catalyst layer slurry;

[0090] 3) spraying the strongly anchored carbon layer slurry prepared in step 1) on the surface of one side of a 72×72 mm proton exchange membrane through a spraying process to form a proton exchange membrane with a high anchored carbon layer load;

[0091] 4) spraying the catalyst layer slurry prepared in step 2) onto the surface of the high anchor carbon layer formed in step 3) on the side away from the proton exchange membrane to form a cathode catalyst layer;

[0092] 5) spraying the catalyst layer slurry prepared in step 2) onto the surface of the other side of the proton exchange membrane to form an anode catalyst layer;

[0093] 6) The gas diffusion layer is respectively mounted on the surface of the cathode catalyst layer and the anode catalyst layer away from the proton exchange membrane, and then divided to form a 25 cm 2 of membrane electrode.

[0094] Comparative Example 1

[0095] This comparative example provides a method for preparing a membrane electrode, comprising the following steps:

[0096] 1) 0.679 g of TKK 47% Pt / C catalyst was moistened with a small amount of water, 4.10 g of Nafion solution and 21 g of isopropanol were added and mixed evenly, and dispersed using a dispersing device to prepare a catalyst layer slurry;

[0097] 2) spraying the catalyst layer slurry prepared in step 1) onto a 72×72 mm proton exchange membrane through a spraying process to form a cathode catalyst layer;

[0098] 3) The catalyst layer slurry prepared in step 2) is prepared on the other side of the proton exchange membrane through a molding process to form an anode catalyst layer;

[0099] 4) The gas diffusion layer is respectively assembled on the surface of the cathode catalyst layer and the anode catalyst layer away from the proton exchange membrane, and then divided to form a 25 cm 2 of membrane electrode.

[0100] The membrane electrodes for proton exchange membrane fuel cells in Examples 1 and 2 and Comparative Example 1 were subjected to durability cycles, and their electrochemical performance changes were measured by polarization curves, and their electrochemical areas were tested by cyclic voltammetry. The results of the electrochemical performance before and after 2000 cycles are shown in Tables 1 and Figures 3 to 6 shown.

[0101] Table 1 Electrochemical performance of membrane electrodes in Examples 1, 2 and Comparative Example 1

[0102]

[0103] Figures 3 to 6 Detailed explanation:

[0104] Figure 3 The membrane electrode durability operating condition diagram provided for Examples 1 and 2 of the present application and Comparative Example 1; Figure 4 Cyclic voltammetry test diagrams provided for Examples 1 and 2 and Comparative Example 1 of the present application; Figure 5 Polarization curve test diagrams provided for Examples 1 and 2 and Comparative Example 1 of the present application; Figure 6 This is a hydrogen permeation current density test diagram provided for Examples 1 and 2 and Comparative Example 1 of the present application.

[0105] Depend on Figures 3 to 6 It can be seen that, compared with before and after 2000 cycles, due to the presence of the high anchored carbon layer, the loss of Pt is suppressed in Examples 1 and 2, and the corresponding ECSA decrease is significantly lower than that in Comparative Example 1, and the corresponding electrochemical performance is significantly higher than that in Comparative Example 1. Finally, the membrane electrode was subjected to an LSV test. Due to the formation of the Pt band, the proton exchange membrane in Comparative Example 1 was significantly degraded, resulting in a significant increase in the hydrogen permeation current density.

[0106] In addition, one or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0107] In an embodiment of the present invention, a strongly anchored carbon layer is provided between the cathode catalyst layer and the proton exchange membrane to solve the problem of performance degradation due to Pt loss and proton exchange membrane degradation caused by the formation of Pt bands during the use of the membrane electrode, thereby improving the utilization rate of Pt and further improving the durability of the membrane electrode of the fuel cell.

[0108] In the embodiment of the present invention, the ECSA attenuation rate of the membrane electrode provided after 2000 cycles is ≤35%, and the rated voltage is ≥0.570V@2000mA / cm 2 , hydrogen permeation current density ≤2.950mA / cm2@0.4V.

[0109] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A cathode composite catalyst layer, It is characterized in that The cathode composite catalytic layer comprises: Strong anchoring carbon layer; the raw materials of the slurry of the strong anchoring carbon layer include: strong anchoring functional material, solvent and Nafion solution, the strong anchoring functional material is a carbon material doped with non-metallic elements; and A cathode catalyst layer; the cathode catalyst layer is disposed on one side of the strongly anchored carbon layer, and the cathode catalyst layer contains a Pt element; Wherein, the strongly anchored carbon layer is arranged between the cathode catalyst layer and the proton exchange membrane.

2. The cathode composite catalyst layer according to claim 1, It is characterized in that The non-metallic elements include one or more of O, N, S and P.

3. The cathode composite catalyst layer according to claim 1, It is characterized in that The carbon material includes: one or more of carbon black, porous carbon, carbon fiber, graphite carbon and carbon nanotube.

4. The cathode composite catalyst layer according to claim 1, It is characterized in that The mass ratio of the strong anchoring functional material to the perfluorosulfonic acid resin in the Nafion solution is 1:(1.0-1.2).

5. The cathode composite catalyst layer according to claim 1, It is characterized in that The raw materials of the slurry of the cathode catalyst layer include: catalyst, Nafion solution and solvent.

6. The cathode composite catalyst layer according to claim 5, It is characterized in that The catalyst includes one or more of a Pt / C catalyst and a Pt alloy catalyst.

7. A method for preparing a cathode composite catalyst layer according to any one of claims 1 to 6, It is characterized in that The method comprises: The strong anchoring functional material is mixed with a solvent and a Nafion solution, and then dispersed to obtain a slurry of a strong anchoring carbon layer; The catalyst is mixed with a solvent and a Nafion solution, and then dispersed to obtain a slurry of a cathode catalyst layer; Applying the slurry of the strong anchoring carbon layer to the surface of one side of the proton exchange membrane to obtain the strong anchoring carbon layer supported on the proton exchange membrane; The slurry of the cathode catalyst layer is coated on the surface of the strongly anchored carbon layer on the side away from the proton exchange membrane to obtain a cathode composite catalyst layer supported on the proton exchange membrane.

8. The method according to claim 7, It is characterized in that The coating is carried out by a spraying process.

9. A membrane electrode, It is characterized in that The membrane electrode comprises: Proton exchange membrane; The cathode composite catalyst layer according to any one of claims 1 to 6; the cathode composite catalyst layer is arranged on one side of the proton exchange membrane; Anode catalyst layer; the anode catalyst layer is arranged on the other side of the proton exchange membrane; Gas diffusion layer; the gas diffusion layer is arranged on a side of the cathode composite catalyst layer and the anode catalyst layer away from the proton exchange membrane.

10. A fuel cell, It is characterized in that The fuel cell comprises the membrane electrode according to claim 9.

Citation Information

Cited By

  • Composite catalyst layer for fuel cell membrane electrode and preparation method and application thereof

    CN121307065A